2000
DOI: 10.1046/j.1365-2222.2000.00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils are a feature of upper and lower airway pathology in non‐atopic asthma, irrespective of the presence of rhinitis

Abstract: These results show that eosinophil infiltration was present in the nasal mucosa of asthmatic patients even in the absence of rhinitis, and add further support to the hypothesis that asthma and rhinitis are clinical expressions of the same disease entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
2
12

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(128 citation statements)
references
References 42 publications
7
107
2
12
Order By: Relevance
“…The coexisting presence of inflammation in the airways in a study on asthmatics with or without rhinitis has been shown by Gaga et al (25). Using biopsies from the nasal mucosa, they showed that eosinophil infiltration occurred in the nasal mucosa of asthmatic patients, irrespective of any signs of rhinitis or not.…”
mentioning
confidence: 70%
“…The coexisting presence of inflammation in the airways in a study on asthmatics with or without rhinitis has been shown by Gaga et al (25). Using biopsies from the nasal mucosa, they showed that eosinophil infiltration occurred in the nasal mucosa of asthmatic patients, irrespective of any signs of rhinitis or not.…”
mentioning
confidence: 70%
“…In patients with moderate-severe asthma, eosinophilic inflammation is more pronounced in the bronchi than in the nose (815), whereas in patients with mild asthma, inflammation appears to be similar in both sites. Moreover, eosinophilic inflammation of the nose exists in asthmatics with or without nasal symptoms (1978).…”
Section: Commonalities and Differences In Mechanisms Between Rhinitismentioning
confidence: 99%
“…However, lower airway epithelial cells are difficult to obtain in a clinical setting, especially from healthy control patients and children. Data from several studies support the premise that epithelial cells from nasal mucosa are a valid and practical proxy for lower airway epithelial cells [13][14][15][16][17][18][19][20] , especially when studying responses to air pollutants and allergens. The nasal mucosa consists of more than 90% ciliated airway epithelial cells and sampling these nasal epithelial cells (NECs) can be readily performed in children as young as age four or five, as it is less invasive than other cell/tissue sampling techniques and is associated with minimal risk of adverse events such as infection [20][21][22][23] .…”
Section: Introductionmentioning
confidence: 94%